Feelings Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
It’s never too early to encourage children to talk about how they feel. This newest title in the Pull and …
Keywords: dept.lib

Who Lives Where? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Sliding panels of animals near and far make for a delightful and satisfying format for matching game fun! Each of …
Keywords: dept.lib

Construction Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Bumpy roads, rough wood beams, and smooth concrete—there’s so much to discover in this Touch and ExploreTM book that’s all …
Keywords: dept.lib

Super Mazes in Space! Translated by Wendeline Hardenberg - Méhée, Loïc (Twirl Books, 2019)
Ten incredible mazes combine with a space adventure to provide a stellar game book for every puzzle-solving kid! Comics artist …
Keywords: dept.lib

Cars Translated by Wendeline Hardenberg - Krasinski, Geraldine (Twirl Books, 2019)
Turn a wheel to see cars of yesteryear, slide a new car onto a car carrier, pull a tab to …
Keywords: dept.lib

Body Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Big, sturdy tabs to push and pull make for great learning fun in this brand-new nonfiction series. Preschool children learn …
Keywords: dept.lib

Pirates Translated by Wendeline Hardenberg - Adams, Ines (Twirl Books, 2019)
Heave ho! Set sail on a high-seas adventure with swashbuckling pirates in search of treasure in this new Magnetology™ title. …
Keywords: dept.lib

Savanna Animals Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Take a trek into the wild . . . • Hunting for food • Building homes • Keeping cool • …
Keywords: dept.lib

Astronauts Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Count down to an incredible voyage! • Learning to pilot a spacecraft • Getting used to being weightless • Going …
Keywords: dept.lib

Jungle Animals Translated by Wendeline Hardenberg - Mazas, Marie (Twirl Books, 2019)
The shaggy fur of a sloth, the scaly skin of an iguana, and the rough hide of a tapir—there’s so …
Keywords: dept.lib

Bathtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
Little Crocodile, Little Monkey, and all their friends can think of a lot more things they’d rather do than take …
Keywords: dept.lib

Ultimate Book of Planet Earth Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2019)
The internationally successful Ultimate Book series expands its scope to embrace-very appropriately-the whole world! The Ultimate Book of Planet Earth …
Keywords: dept.lib

Badadoom Badabump! Translated by Wendeline Hardenberg - Baou, Bartélémi (Twirl Books, 2019)
Inspiring imagination and encouraging hours of creative play, Badaboom Badabump! is an innovative play set that not only includes a …
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib